MoCN catalyst functionalized SnO₂-Sb/Ti anode enhanced electrochemical oxidation degradation of diclofenac: Performance, mechanism, and toxicity evolution - YuRui Yuan; Zihao Ye; Yuan Wu; Yan Zhang (Journal of Environmental Chemical Engineering, 2026)

Isolation of reassortant H5N1 and H5N8 avian influenza viruses from co-infections and their host-dependent replication dynamics - Yuwei Wu; Nuo Xu; Zhifan Li; Zijun Lu; Yurui Dong; Yijie Guo; Ying Bian; Kunlin Li; Chenzhi Huo; Tao Qin; Sujuan Chen; Hui Yang; et al. (Veterinary Microbiology, 2026)

The global APSES transcription factor PeStuA modulates growth, development, stress response, hydrophobicity, patulin biosynthesis and pathogenicity in Penicillium expansum - Yanling Wang; Yurui Wu; Qianrun Liang; Xin Chen; Jinfen Zhu; Wei Li (International Journal of Food Microbiology, 2026)

Oxidizing agents alter surface reaction pathways in heterogeneous Fenton reactions: Surface electron transfer interactions and altered bond breaking processes in contaminants - Yurui Li; Haoran Wu; Bing Yang; Chao Zhu; Shijie Zhou; Lili Ma; Lingli Li; Mingyan Chen; Heng Guo; Yucheng Liu (Journal of Environmental Chemical Engineering, 2025)

B-Mg co-substituted binder-free ZSM-5 zeolites with recrystallized cheese-like hierarchical porosity for enhanced benzene-methanol alkylation: Synergistic micro-meso-macroporous mass transfer and acid-site engineering - Run Cai; Likun Wen; Yihua Cao; Yindan Wu; Yichen Song; Xinyu Wang; Hanyang Zhou; Yurui Zhang; Xiaoping Dai; Xin Zhang (Chemical Engineering Journal, 2025)

Manganese in drinking water distribution systems: A comprehensive review on the occurrence, migration transformation mechanisms, and control strategies - Yuan Wu; Yan Jia; Zhihui Hu; Yurui Yuan; Yan Zhang (Critical Reviews in Environmental Science and Technology, 2025)

Significantly enhanced piezoelectric properties of BaTiO3-based ceramics with unchanged curie temperature via local chemical inhomogeneity - Ming Wu; Ruifeng Yao; Chengyichang Jin; Yurui Xu; Jingzhe Xu; Liqiang He; Yang Yang; Yongbin Liu; Lisheng Zhong; Jinghui Gao (Chemical Engineering Journal, 2025)

Preparation of K-carrageenan /polylactic acid nanofiber membranes encapsulating Vitamin C/ Hydroxypropyl-beta-cyclodextrin inclusion complexes by electrostatic spinning for blueberry preservation - Lingling Bai; Yurui Wu; Huijin Xu; Jiyuan Yang; Yiting Lu; Wenge Yang; Yonghong Hu (Food Bioscience, 2025)

Electrostatic spinning construction of GA/HP-β-CD functionalized COS/PLA composite membrane for cherry tomato preservation applications - Wenge Yang; Jiaxing Hao; Yurui Wu; Yuheng Zhou; Li Mi; Yonghong Hu (Food Packaging and Shelf Life, 2025)

Effect of CFEM proteins on pathogenicity, patulin accumulation and host immunity of postharvest apple pathogens Penicillium expansum - Yanling Wang; Jie Gao; Xin Chen; Yanqi Huang; Yurui Wu; Jinfen Zhu; Wei Li (International Journal of Food Microbiology, 2025)

The clinical characteristics of Streptococcus equi ssp. zooepidemicus causing acute death in pigs and its prevention with chimeric monoclonal antibodies - Chen Yuan; Yuchang Wang; Xiaowen Zhang; Xingyu Tian; Ying Liang; Fei Pan; Haoshuai Song; Linya Xia; Zhihui Wu; Wenqing Wang; Xiaowen Zhang; Yurui Xie; et al. (Veterinary Microbiology, 2025)

PCL/soy peptide nanofibers incorporated with riboflavin/HP-β-CD assemblies for improving fruit storage quality - Wenge Yang; Aili Wang; Yurui Wu; Yuheng Zhou; Yonghong Hu (Food Chemistry, 2025)

Design of Ni-based heterostructured catalyst with Ni3+ for enhanced bidirectional sulfur conversion - Yurui Wu; Wei Li; Hengzhi Liu; Yufang Chen; Manfang Chen; Xingqiao Wu; Yunfeng Peng; Wenlong Xia; Yuchao Du; Keyang Fu; Xiukang Yang; Xianyou Wang; et al. (Chemical Engineering Journal, 2025)

A flexible, highly sensitive, and anti-strain interference sensing fabric based on conjugated electrospinning core–shell conductive nanofiber yarns for ultra-stable pressure sensing and human–machine interaction - Wenqi Wu; Xu Jin; Adilaimu Tiliman; Fan Zhang; Ge Bai; Yurui He; Gaoling Jin; Bin Wang; Xiuqin Zhang; Rui Wang (Chemical Engineering Journal, 2025)

CuFeS2/GAC particle combined with electrochemical activation of persulfates for efficient degradation of carbamazepine - YuRui Yuan; Xincheng Ye; Yan Jia; Yuan Wu; Yan Zhang (Chemosphere, 2024)

Thermal properties and grey correlation degree analysis of tar-rich coal under cryogenic and pyrolysis condition - Tao Xu; Yurui Lei; Lingyun Chen; Yongping Wu (Fuel, 2024)

Effects of Environmental Enrichment on the Growth, Gonadal Development, and Welfare of the Chinese Hooksnout Carp (Opsariichthys bidens) - Yurui Lin; Qianhui Li; Zhuo Cai; Jiazheng Ye; Wanqing Tong; Siqi Ren; Xinrui Wu; Huixian Chen; Meidi Lü; Shanjian Zheng (Fishes, 2024)
To investigate the effects of environmental enrichment on the growth and welfare level of the Chinese hooksnout carp (Opsariichthys bidens), an experiment was carried out for 56 d with four types of enrichment environments: low-density physical enrichment, high-density physical enrichment, low-density social enrichment, and high-density social enrichment. The experimental results revealed that both physical and social enrichment treatments positively affected the growth and gonadal development of O. bidens. The physical enrichment treatment was found to increase the antioxidants’ content, such as CAT, SOD, and GSH, in the liver of O. bidens. Moreover, this treatment was able to lead to a reduction in MDA content and enhancement of the fish’s antioxidant capabilities. Behavioral observations, cortisol level analysis, and pcna gene expression analysis indicated that the physical enrichment treatment redused the clustering, aggression, and stress behaviors of O. bidens, maintaining them in a low-stress state. In most respects, the high-density physical enrichment has more positive effects than the low-density one. In contrast, the social enrichment treatments resulted in higher stress levels for O. bidens.

Occurrence states and migration of water during the evaporation of desulfurization wastewater - Lingxiao Zhan; Dawei Hou; Heng Chen; Yurui Wang; Suoqi Zheng; Zhihao Li; Hao Wu; Haijie Chen; Xiaoyue Ma; Linjun Yang (Desalination, 2024)

Effects of exogenous steroid hormones on growth, body color, and gonadal development in the Opsariichthys bidens - Qingyuan Liu; Jinchun Hu; Yurui Lin; Xinrui Wu; Yujun Feng; Jiazheng Ye; Kai Zhang; Shanjian Zheng (Fish Physiology and Biochemistry, 2024)

Hypoxia Potentiated Lung Cancer Cell Migration and Invasion by up-regulating HIF1α/JAK2/STAT3 Axis and Activating MMP13 Transcription - Xiaoju Cheng; Damin Liang; Xiaoqian Li; Chengmin Deng; Meng Ye; Jiao Yang; Yurui Liu; Kaifeng Wu; Jie Wu; Peng Tian (Cell Biochemistry and Biophysics, 2024)

Ammonia release characteristics during desulfurization wastewater evaporation: Mechanisms and implications - Heng Chen; Dawei Hou; Zhihao Li; Lingxiao Zhan; Lijian Jin; Suoqi Zheng; Yurui Wang; Hao Wu; Ning Zhao; Liliang Lin; Linjun Yang (Journal of Water Process Engineering, 2024)

Copolymer-grafted cellulose nanocrystal induced nanocomposite hydrogels with enhanced strength, high elasticity and adhesiveness for flexible strain and pressure sensors - Bengang Li; Yurui Chen; Wei Wu; Xuzhi Cao; Zhenyang Luo (Carbohydrate Polymers, 2023)

Cold-resistant performance and the promoted development of functional community with flexible metabolic patterns in a Biofilm Bio-Nutrient Removal (BBNR) system amended with supplementary carbon source for phosphorus recovery - Pengbo Jiao; Qing Tian; Sand Wolfgang; Xuetong Dong; Yurui Wu (Environmental Research, 2023)

Evaluation Climate Change Impacts on Water Resources Over the Upper Reach of the Yellow River Basin - Xiaowen Zhuang; Yurui Fan; Yongping Li; Chuanbao Wu (Water Resources Management, 2023)

Design and testing of a mechanized brush-screen cooperative vibration harvester for mudflat-buried shellfish based on the discrete element method - Hangqi Li; Gang Mu; Hanbing Zhang; Hao Wu; Fawei Liu; Zhenyin Sun; Qian Zhang; Yizhou Wang; Yurui Wang; Xiuchen Li; Guochen Zhang (Frontiers in Marine Science, 2023)
Introduction To enhance the application of mechanized harvesting and supplement research on harvesting theory in mudflat-buried shellfish harvesting in China, a brush-screen cooperative mudflat-buried shellfish vibration harvester was designed. Methods The harvester is primarily composed of a crank rocker double-layer vibrating screen, two stage rolling brush, and a conveyor chain. White clams ( Mactra veneriformis ) cultured in mudflats were used as the research objects in this paper, and the mechanics and motion states of the shellfish on the vibrating screen were analyzed. The shellfish harvesting simulation response surface experiments based on the discrete element method (DEM) were conducted to analyze the influence of the main operating parameters on the quantity of shellfish harvested. Results The results revealed that the number of shellfish harvested was significantly influenced ( p < 0.01) by vibrating screen amplitude, first-stage spiral rolling stainless steel brush rotation rate, and harvester travel speed. The optimal combination of key parameters was 1.4 mm, 40 rpm, and 10 m/min, respectively. With these values, the projected shellfish crushing rate was 2.82% and the shellfish harvesting efficiency was 125 pieces/m 2 . The equipment was then manufactured and the shellfish harvesting verification test was performed under the same operating parameters as the simulation. Test results indicated that the harvesting efficiency of the equipment was 114 pieces/m 2 and the shellfish crushing rate was 6.97%. Discussion The shellfish harvesting work could be completed by the equipment effectively and with low loss. The results of this study provide a theoretical reference for a novel mechanized method of harvesting mudflat-buried shellfish.

The VALiDATe29 MRI Based Multi-Channel Atlas of the Squirrel Monkey Brain - Kurt G. Schilling; Yurui Gao; Iwona Stepniewska; Tung-Lin Wu; Feng Wang; Bennett A. Landman; John C. Gore; Li Min Chen; Adam W. Anderson (Neuroinformatics, 2017)